04 DIAGNOSTIC ACCURACY OF THE SERUM-BASED MUCOSAL HEALING INDEX ASSAY IN CROHN'S DISEASE AND COMPARATIVE ACCURACY TO FECAL CALPROTECTIN IN ROUTINE PRACTICE. (7th February 2019) - Battat, Robert; Boland, Brigid; Singh, Siddharth; Collins, Angelina; Evans, Elisabeth R; Valasek, Mark A; Jain, Anjali; Sandborn, William J; Dulai, Parambir S
Abstract: Background & Aims: Biomarker-based management improves outcomes in Crohn's disease (CD) compared to symptoms alone, but existing biomarkers have limitations. We assessed the diagnostic performance of the Mucosal Healing Index (MHI; PROMETHEUS MonitrTM) for detecting mucosal inflammation in CD. Methods: Serum, stool, and blinded disease activity data (clinical, endoscopic and histologic) were used from a prospectively maintained single-center biobank. MHI diagnostic accuracy (area under the receiver operating curve: AUROC) was assessed for endoscopic remission (ER; SES-CD ≤2, ≤1 per segment) and MH (ER + histologic remission: GHAS≤2) and were compared to fecal calprotectin (FC). Responsiveness (Spearman's correlations) was assessed for changes in MHI, FC, and symptoms, to SES-CD. Results: 211 patients with 290 endoscopic assessments were included. Symptom based indices had high diagnostic misclassification rates. AUROC estimates for the MHI were 0.70 for ER (95%CI 0.64-0.76) and 0.69 for MH (95%CI 0.59-0.79). The established MHI cutoff (>50) had 100% specificity for confirmation of mucosal inflammation. An MHI cutoff of 20 had 83% sensitivity for excluding mucosal inflammation. The comparative diagnostic accuracy of MHI to FC using matched samples (119 assessments) was not significantly different (ER: AUROC 0.78 vs. 0.84, p=0.35; MH: AUROC 0.76 vs. 0.80, p=0.61). MHI was responsive to changes in SESCD (r = 0.34, p=0.01), whereas symptoms (r = 0.18, p=0.42) and FC were not (r =0.17, p=0.61). Conclusion: The MHI, a serum-based biomarker test for CD, has good diagnostic accuracy for mucosal inflammation, was comparable to FC, and was responsive to changes in endoscopic disease activity. Further studies should validate comparative responsiveness between MHI, FC and symptoms. Sensitivity, Specificity, Positive and Negative Likelihood Ratios for MHI